Psychological Aspects of Vocational Maturity: Implications for Counselling - Krebs, Elfriede (Canadian Journal of Counselling and Psychotherapy, 2011)
In order to better identify and master specific developmental stages and tasks necessary for the enhancement of vocational maturity of adolescents, this article discusses the relationship between vocational maturity and a set of developmental and/or psychological characteristics —moral development and social interest. The sample of 240 adolescents included all of the students enrolled in the ninth- and twelfth-grade classes of a high school in Winnipeg, Canada. A sketched literature review of vocational maturity as well as the definitions of the vocational, social, and moral developmental tasks are presented. This is followed by a brief description of the sample design, instrumentation, statistical methodology, and results of the study. The conclusions and counselling implications suggest that vocational maturity is significantly correlated with social interest and moral development. These are three developmental tasks of adolescence which are interrelated processes which cannot be isolated from one another or from other aspects of the adolescent's development.